The Impact of The Adopted Accounting Policy on The Results of The Financial Analysis- Decisions of Individuals Under Conditions of Uncertainty - Marek WIERZBIŃSKI; Zofia WIERZBIŃSKA (Communications of International Proceedings, 2023)
The purpose of this paper is to present the impact of the adopted accounting policy and its impact through the financial statements on the results of the financial analysis - by influencing the base data used in this analysis. The issues presented in the paper are issues in the area of individuals' decision-making allowed by law - and they still provide the entity with tools to improve its "financial image". Deliberate, aggressive data distortions would have a far-reaching impact.
Keywords: accounting policy; financial analysis; financial reporting; profitability; liquidity